BUSINESS RISK MODERATES GREEN ACCOUNTING AND INDEPENDENT BOARD OF COMMISSIONERS WITH FINANCIAL PERFORMANCE - Arum Wulandari; Holiawati; Nofryanti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to investigate the direct effects of Green Accounting (GA) and Good Corporate Governance (GCG) on the Financial Performance (FP) of Indonesian firms and to examine the moderating role of Business Risk (BR) in these relationships. Grounded in Signaling Theory, the research addresses the inconsistent findings in prior literature by introducing a critical contextual factor. A quantitative research design was employed using a balanced panel dataset of 25 companies participating in Indonesia's PROPER program and listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, yielding 125 observations. Data were analyzed using panel data regression with the Common Effect Model (CEM) selected as the most appropriate estimator following Chow, Hausman, and Lagrange Multiplier tests. Classical assumption tests confirmed the model's robustness and freedom from econometric issues. The results indicate that both Green Accounting (β = 0.590, p < 0.01) and Good Corporate Governance (β = 3.054, p < 0.01) have a significant positive effect on Financial Performance. Furthermore, Business Risk does not moderate the GA-FP relationship (β = 0.683, p > 0.05), suggesting the value of environmental signaling is risk-resilient. Conversely, Business Risk significantly and positively moderates the GCG-FP relationship (β = 17.399, p < 0.01), indicating that strong governance becomes exponentially more valuable in high-risk environments. The findings guide managers to invest in green accounting as a stable strategy for enhancing reputation and performance and to reinforce corporate governance structures as a primary defense mechanism during periods of high uncertainty. Policymakers can use these insights to encourage broader adoption of sustainability and governance practices. This study contributes to the literature by integrating environmental, governance, and risk management perspectives within a unified framework. It provides novel empirical evidence on the differential moderating effect of business risk, demonstrating that the signaling power of environmental practices is stable, while the value of governance signals is contingent on risk conditions.